Cisplatin reacts with histone H1 and the adduct forms a ternary complex with DNA. Issue 3 (23rd January 2019) - Cheng, Lanjun; Li, Chan; Xi, Zhaoyong; Wei, Kaiju; Yuan, Siming; Arnesano, Fabio; Natile, Giovanni; Liu, Yangzhong
Abstract : The histone H1 readily reacts with cisplatin and the adduct can form H1–cisplatin–DNA ternary complexes. Interestingly, cisplatin is more prone to form H1–Pt–DNA ternary complexes than trans -oriented platinum agents. Abstract : Cisplatin is an anticancer drug widely used in clinics; it induces the apoptosis of cancer cells by targeting DNA. However, its interaction with proteins has been found to be crucial in modulating the pre and post-target activity. Nuclear DNA is tightly assembled with histone proteins to form nucleosomes in chromatin; this can impede the drug to access DNA. On the other hand, the linker histone H1 is considered 'the gate to nucleosomal DNA' due to its exposed location and dynamic conformation; therefore, this protein can influence the platination of DNA. In this study, we performed a reaction of cisplatin with histone H1 and investigated the interaction of the H1/cisplatin adduct with DNA. The reactions were conducted on the N-terminal domains of H1.4 (sequence 1–90, H1N90 ) and H1.0 (sequence 1–7, H1N7 ). The results show that H1 readily reacts with cisplatin and generates bidentate and tridentate adducts, with methionine and glutamate residues as the preferential binding sites. Chromatographic and NMR analyses show that the platination rate of H1 is slightly higher than that of DNA and the platinated H1 can form H1–cisplatin–DNA ternary complexes. Interestingly, cisplatin is more prone to form H1–Pt–DNA ternary complexes than trans -oriented platinum agents. The formation of H1–cisplatin–DNA ternary complexes and their preference for cis - over trans -oriented platinum agents suggest an important role of histone H1 in the mechanism of action of cisplatin.